Improving Students' Reading Skills Through Project-Based Learning Methods - Indri Willa Saputri; Yufi Latmini Lasari (Yayasan Dinamika Ilmu Banyuwangi, 2025)
This study aims to develop and test the effectiveness of the project-based learning model in improving the reading skills of Class IV students of SD N 06 Cubadak, West Sumatra. This study uses the Classroom Action Research method consisting of two cycles as an effort to improve students' reading skills through the project-based learning method in Class IV of SD N 06 Cubadak. This classroom action research took place in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The study was conducted in Class IV of SD N 06 Cubadak, West Sumatra from September 2023 to November 2023. The subjects of the study were all students of class IV of SD N 06 Cubadak in the 2023/2024 academic year totaling 32 students. The object of the study was Indonesian reading skills. The results of the study showed that: students' reading skills on the SPOK material increased in cycle I showing an average score of 75 with 60% of them reaching the KKM score, and in cycle II showing an average score of 85 with 85% of them reaching the KKM score. Thus, the application of the project-based learning model can improve students' reading skills in two cycles. Among the changes in students' reading skills are indicated by their ability to master the conditions and meanings of the reading they read, and can relate data from various sources, participation in project-based learning methods makes students more motivated to read more often and more critically, due to the need to find relevant data to complete this method. Among the factors that influence the improvement of reading skills are active participation, collaboration, relevance of materials, and teacher support.